CU-SIL DENTURE AS A TRANSITIONAL PROSTHESIS TO PRESERVE THE REMAINING NATURAL TEETH USING PERMANENT SILICONE LINER - S, Divakar; Rathee, Manu; Chahal, Sujata; Singh, Sandeep (Interdental: Jurnal Kedokteran Gigi, 2021)
The goal of modern dentistry is to be conservative, preserving teeth but also maintaining the stability of the remaining alveolar ridge and the periodontium's proprioceptive capabilities. Cu-sil denture is the simplest approach in the preservation of teeth and maintaining proprioception. It is a type of transitional denture that provides an alternative treatment plan for the patients willing to replace their missing teeth while retaining their remaining natural teeth. It gives potential psychological benefits to the patients by avoiding extractions. It's a tissue-bearing acrylic appliance with a soft viscoelastic wrap that clasps the neck of each dentition, sealing out food and water simultaneously protecting and splinting each remaining tooth from the rigid acrylic denture base. This case reports series describes chairside techniques to fabricate Cu-sil dentures in the usual dental set-up.